Orally administered fluorescein angiography for ultra-wide-field imaging: is a safe and effective modality across different age groups and fundus diseases? - Ji, Yuke; Hu, Xinya; Hu, Yuting; Lai, Sisi; Lu, Xiaofeng; Li, Xuan; Liu, Zixiao; Zhang, Shaochong; Yang, Weihua; Yao, Xue (Frontiers in Cell and Developmental Biology, 2026)
PurposeTo comprehensively evaluate the clinical utility, imaging performance, and safety of orally administered fluorescein angiography (oral FA) combined with an ultra-wide-field imaging system in the diagnosis and management of fundus disorders.MethodsThis prospective study enrolled 382 patients (676 eyes) aged 4–83 years, comprising 164 females and 218 males. All participants underwent oral FA after ingesting a weight-based dose of fluorescein sodium. Anonymized peak-phase images were independently graded by four retina specialists using a standardized three-parameter scoring system. Images were classified as high, moderate, or poor quality based on total scores. Circulation times (first appearance time, detailed visualization time, and optimal visualization time) and adverse events were systematically recorded. Statistical analyses assessed differences in image quality and timing across age groups and disease categories.ResultsOral FA was successfully performed in all cases. Among 676 eyes, 662 (97.9%) were graded as high quality, 12 (1.8%) as moderate quality, and 2 (0.3%) as poor quality. Clinically useful images were obtained in 99.7% of cases. No significant differences in image quality or circulation times were observed across age groups. However, image quality was significantly higher in retinal degenerative diseases compared to retinal vascular diseases (P = 0.001), though both groups maintained diagnostically adequate scores. In addition, no significant differences in circulation times (first appearance time, detailed visualization time, and optimal visualization time) were observed among any disease groups. Mild adverse events (nausea, rash) occurred in only 2.1% of patients, with no severe reactions—even in six patients with prior intravenous FA (IVFA) allergy history.ConclusionOral FA is a well-tolerated and clinically effective imaging modality that produces high-quality, diagnostically reliable angiograms across all age groups and multiple retinal disease categories. Its non-invasive nature, excellent safety profile, and ability to visualize peripheral pathology support its use as a practical and valuable alternative to conventional IVFA, particularly in pediatric, needle-phobic, or allergy-prone populations.